2021
DOI: 10.1016/j.jbc.2021.100802
|View full text |Cite
|
Sign up to set email alerts
|

The tail of chlorophyll: Fates for phytol

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Phytol is derived from the hydrolysis of chlorophyll and is a side chain of chlorophyll prenyl bound to ester bonds (Gutbrod, 2019). In plants, phytol is used to synthesize tocopherol (vitamin E), or phylloquinone (vitamin K) (Durrett, 2021). Phytol is known to have antianxiety, cytotoxic, metabolism-modulating, antioxidant, apoptosis, antinociceptive, antiinflammatory, immunomodulatory, and antimicrobial effects (Islam, 2018), antihyperalgesic, anti-inflammatory, and antiarthritis (Carvalho, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Phytol is derived from the hydrolysis of chlorophyll and is a side chain of chlorophyll prenyl bound to ester bonds (Gutbrod, 2019). In plants, phytol is used to synthesize tocopherol (vitamin E), or phylloquinone (vitamin K) (Durrett, 2021). Phytol is known to have antianxiety, cytotoxic, metabolism-modulating, antioxidant, apoptosis, antinociceptive, antiinflammatory, immunomodulatory, and antimicrobial effects (Islam, 2018), antihyperalgesic, anti-inflammatory, and antiarthritis (Carvalho, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Its chemical structure includes a porphyrin ring with a central magnesium ion, and an attached hydrocarbon tail known as a phytol. The porphyrin ring is made up of four nitrogen-containing groups called pyrrole, and the phytol tail is composed of isoprenoid units [ 7 ]. Chlorophyll a absorbs light most efficiently in the red and blue regions of the spectrum, with peak absorption at around 430 and 662 nanometers, respectively.…”
Section: Chlorophyll: Chemical Properties and Metabolismmentioning
confidence: 99%
“…On the other hand, mass-spectrometry experiments indicate the main breakdown products of the prenyl side chain are phytols ( Mach, 2015 ). Although studies have suggested that the phytol degradative pathway can provide substrates for respiration during sugar starvation ( Ishizaki et al, 2005 ), components of the phytol catabolic pathway have not been identified ( Durrett and Welti, 2021 ). Phytol might be degraded to phytenal which accumulates in senescing oat leaves and then to phytanoyl-CoA via unknown steps ( Ishizaki et al, 2005 ).…”
Section: Potential Respiratory Substratesmentioning
confidence: 99%
“…In mammalian catabolic pathways, phytanoyl-CoA undergoes α-oxidation and β-oxidation in peroxisomes and mitochondria ( Kohlmeier, 2015 ; Durrett and Welti, 2021 ; Gutbrod et al, 2021 ). In plants, phytanoyl-CoA hydroxylase and 2-hydroxy-phytanoyl-CoA lyase have been localized to peroxisomes and characterized to be the main pathway of phytanoyl-CoA metabolism ( Araújo et al, 2011a ; Yang et al, 2022 ).…”
Section: Potential Respiratory Substratesmentioning
confidence: 99%